The Effects of Growth, Size and Capital Structure Decisions on Profitability in Istanbul Stock Exchange (ISE):2008-2017 (International Journal of Scientific Research and Management (IJSRM), 2020)
The effect of firm size, growth and capital structure on firm profit rates has been searched by economists for several decades. The aim of this paper is to investigate the impacts of size, liquidity, growth and capital structure decisions on profitability in Stock Exchange Istanbul (BIST). For this aim, annual data of 114 manufacturing industry companies which are active at the moment in BIST. The financial data set covers the period 2005-2017. Results of the study using panel data analysis shows that while the ratios with regarding capital structure decisions negatively affect profitability, whereas size liquidity and growth positively affects profitability.